2016
DOI: 10.1177/1010539516667782
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Work-Family Role Conflict and Its Impact on Professional Women in Medicine, Engineering, and Information Technology in Nigeria

Abstract: This study examines work-family role conflict and the factors predicting it, with a sample of 173 professional women in engineering and information technology (IT) firms, including 2 hospitals-1 public and 1 private. Our findings show no significant difference in the level of work-family role conflict encountered by women across medicine, engineering, and IT, whereas hours of work, family responsibilities, job demand, and work role overload were significantly correlated with work-family role conflict. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The biological timing of the maternal role, a crucial life course milestone, often coincides with the start of a dental career. Our finding that most mothers found it difficult to balance young children and work is comparable to studies from different countries and cultures [23] [24] [25]. The timing of this universal life stage plays a decisive role for women dentists.…”
Section: Discussionsupporting
confidence: 83%
“…The biological timing of the maternal role, a crucial life course milestone, often coincides with the start of a dental career. Our finding that most mothers found it difficult to balance young children and work is comparable to studies from different countries and cultures [23] [24] [25]. The timing of this universal life stage plays a decisive role for women dentists.…”
Section: Discussionsupporting
confidence: 83%
“…Azodo and Ezeja [12] also showed that 1 in every 10 respondents reported severe occupational stress in Nigeria. According to Uzoigwe et al, [13] the workers are burdened by work demands, which invariably affects the work–family role conflict they experience and leads to deterioration of their occupational health.…”
Section: Introductionmentioning
confidence: 99%
“…This could be because being head of household involves dealing with various responsibilities and participating in problem-solving, both at home and work. Many of the participants who are heads are not only responsible for the care of the home but also for the care of the husband and children, as well as job responsibilities, which could exacerbate role conflicts 13 . According to Díaz and Mauro 24 , a large propor-tion of female workers in the health area report a very high workload, exceeding 60 weekly hours of domestic work and paid work, which could amount to more than 12 hours per week of unpaid work alone.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the highest concentration serves as nursing assistants, also known as paramedical technicians or nursing technicians, who are responsible for the implementation of basic nursing activities, and these professionals gather the most significant number of absenteeism cases 10 . This population consists mainly of women 11 , with usually higher levels of absenteeism than men 12 , and who are also subject to a higher level of burden since they respond both to their work obligations and family and domestic demands 13 . However, it is a rarely studied population, which has grown considerably in recent years, showing an increase of more than 23% 11,14 , and is generally exposed to excessive workload and a fast and intense work pace 15 .…”
Section: Introductionmentioning
confidence: 99%